A Double-Edged Sword of Humour: Students’ Perspectives on Teachers’ Use of Humour in EFL Classroom - Rianita, Dian; Sari, Fara Merian; Yandra, Alexsander (REiLA : Journal of Research and Innovation in Language, 2023)
Humour has varied functions in teaching and learning English as a Foreign Language (EFL), particularly in enhancing classroom instruction. This study investigates EFL students' perspectives on their lecturers' use of humour, focusing on students from private universities. The study employed a mixed-method approach, gathering data through questionnaires from 122 students and conducting in-depth interviews with 5 students. This diverse sample included learners aged 18 to 45 years, offering insights into a broad age range. Findings indicate that humour in the EFL classroom positively influences students' learning experiences. It contributes to a relaxed learning atmosphere, fosters closer connections between students and lecturers, and enhances engagement with the material. However, it's crucial that the humour aligns with the adult status of the students, indicating a need for sensitivity and appropriateness. The study underscores humour's dual role in EFL education, akin to a double-edged sword with both positive and negative impacts. From the perspective of private university students, appropriate humour is key to effective learning, particularly for adult learners. The findings suggest that while humour can be a powerful pedagogical tool, it must be employed judiciously, considering the varied age and backgrounds of the learners. The implications extend to the broader context of EFL education in higher learning, highlighting the importance of lecturer-student dynamics and the careful integration of humour in educational settings.